Mastering the Basic Content Knowledge in Higher Order Thinking Skills Among Teachers in Malaysia in Teaching and Learning Process - M.Gunahlan, Vikneswaran; H.Iksan, Zanaton (Proceedings of the UR International Conference on Educational Sciences, 2018)
Malaysia education system has undergone a major change by adopting a new policy known as the Malaysian Education Development Plan (PPPM) 2013 to 2025. In this policy, various issues have been emphasized to improve the education system in our country to compete with the more developed countries. The main thing to emphasize in this system is the high order thinking skills. In this context the teacher plays an important role in applying the element. Unfortunately, most of the teachers fail to play the role. The purpose of this research is to find out the basic things in the implementation of HOTS, namely knowledge, application, determination among teachers and readiness of among students towards higher order thinking skills (HOTS) in Negeri Sembilan (one of state in Malaysia) in teaching and learning process. A total of 120 Mathematics and Science teachers at all levels involved. The sample of the study is selected at random. The findings were analyzed using SPSS descriptive form, percentage, mean and frequency and intervention. The findings show that teacher knowledge on HOTS and application of HOTS in the teaching and learning process is low that is below 50%. While the application of students in HOTS and teachers efforts to know about HOTS also show at very low percentage that is below 30%. These results indicate that many teachers are still poor in the contain knowledge of HOTS cause the student achievement is very low and difficult to achieve PPPM objectives. Therefore, the ministries and education departments should take this into account in order to organize workshops or build a module related to KBAT as a guide to help teachers understand and apply the skills in the teaching and learning process.